The Influence Of Geothermal Environment To The Quality Of Porcelain Insulator: A Gap Analysis - Nur Syahidah, Yusoff; Maman Abdurachman, Djauhari (IEEE, 2012)
It is assumed that polluted environment reduces the quality of porcelain insulator in terms of leakage current. In our previous study, a correlation analysis was conducted to show the influence of geothermal area to the quality of porcelain insulator. In this paper a further analysis based on gap analysis is conducted to have a better understanding about what quality characteristics that are more sensitive to the environment.